Early Introduction of Everolimus Immunosuppressive Regimen in Liver Transplantation with Extra-Anatomic Aortoiliac-Hepatic Arterial Graft Anastomosis - Felli, Emanuele (Hindawi Publishing Corporation, 2014)
Liver transplantation is the treatment of choice for patients with acute and chronic end-stage liver disease, when no other medical treatment is possible. Despite high rates of 1- to 5-year survival, long-term adverse effects of immunosuppressant agents remain of major concern. Current research and clinical efforts are made to develop immunosuppressant agents that minimize adverse effects along with a low rate of graft rejection. Tailoring immunosuppressive therapy to individual patients by the use of proliferation signal inhibitors seems to be the best way to minimize toxicity and increase efficacy. Recently everolimus has been introduced in clinical practice; among its adverse effects an increased incidence of arterial graft thrombosis in renal transplants, vascular anastomosis leakage, impaired wound healing, and thrombotic microangiopathy have been reported. We present the case of a 54-year-old patient submitted to liver transplantation for end-stage liver disease treated by an extra-anatomic aortoiliac-hepatic arterial graft anastomosis and early postoperative introduction of everolimus for acute renal failure. Postoperative period was characterized by two abdominal collections and reactivation of cytomegalovirus infection that were treated by percutaneous drainage and antiviral therapy, respectively; the patient is well after 8-month followup with patency of the arterial conduit and no leakage.